Identification and characterization of novel type of RNAs, circRNAs in crucian carp Carassius auratus gibelio. Issue 94 (November 2019) - Hu, Xiaolong; Dai, Yaping; Zhang, Xing; Dai, Kun; Liu, Bo; Yuan, Rui; Feng, Yongjie; Liang, Zi; Zhu, Min; Zhang, Mingtian; Zhang, Yunshan; Zhang, Ziyao; et al.
Abstract: Circular RNAs (circRNAs) with regulatory potency activity was identified from varieties of species. Crucian carp ( Carassius auratus gibelio) is one of the most freshwater aquaculture species in China. Every year, huge economic damage to the farming was caused by the virus and bacterial infection. Until now, there is any information about circRNA reported from the Crucian carp. In this study, the expression pattern of circRNA in Crucian carp was investigated with transcriptomic analysis. The results showed that only 37 circRNAs were identified from the Crucian carp, and these circRNAs biogenesis was formed with canonical GU-AG splicing mechanism with unevenly distributed on the chromosomes. Wherein, most of the circRNAs were derived from the sense overlapping strategy. Reverse transcript PCR and Sanger sequencing data indicated that these circRNAs were existed authenticity in Crucian carp. The bioinformatics analysis indicated that circRNAs identified from the Crucian carp with potential miRNA sponge regulate the expression level of mRNAs. GO annotation and KEGG pathway analysis of these circRNAs showed that more than 20% circRNAs were related with catalytic activity and binding in the category of molecular function, and these circRNAs were enriched in 9 signaling pathways, such as, Wnt signaling pathway, MAPK signaling pathway, Ubiquitin mediated proteolysis et al. 220 mRNAs would be regulated by the circRNAs via miRNAs mediation. These target mRNAs were further analyzed with functional annotation and KEGG analysis. GO annotation analysis showed that several genes were related with function of nucleotide binding, transcription regulatory activity. KEGG pathway analysis showed that 5 genes were enriched in the pathway of Endocytosis. The circRNA-miRNA-mRNA regulation network indicated that one miRNA can link one or more circRNA and one or more mRNA. Overall, these results will not only help us to further understand the novel RNA transcripts in Crucian carp, but also provide the novel clue to investigate the interaction between host and pathogens from this novel circRNA molecule. Highlights: CircRNAs were identified from the Crucian carp with transcriptomic analysis. CircRNAs biogenesis was formed with canonical GT/AG splicing mechanism. Most of the circRNAs were derived from the sense overlapping strategy. These circRNAs were enriched in 9 signaling pathways. The circRNA-miRNA-mRNA regulation network was constructed.